Symbolic Violence of Dropadi Figure in Novel Pertempuran Lain Dropadi by Triyanto Triwikromo - Dyah Ayu Widyawati Cahyono Putri; Teguh Supriyanto; Mukh Doyin (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The issue of symbolic violence against women is often found in literary works in the form of prose, namely novels. The aim of this research is to describe the form of symbolic violence against the character Dropadi in the novel Pertempuran Lain Dropadi by Triyanto Triwikromo. This research uses two research approaches, namely a theoretical approach and a methodological approach. The theoretical approach in this research uses a literary sociology approach, while the methodological approach is a qualitative descriptive approach. The data in this research is in qualitative form in the form of sentence fragments or speech texts that reflect violence against the character Dropadi in the novel Pertempuran Lain Dropadi by Triyanto Triwikromo. The data collection technique used in this research is a semiotic reading technique, namely heuristic reading. Next, the data was analyzed using hermeneutic reading techniques. The results of research on symbolic violence studied using Pierre Felix Bourdieu's power structure theory are 1) habitus, 2) capital, 3) arena or field experienced by the character Dropadi in the novel Pertempuran Lain Dropadi by Triyanto Triwikromo.